'Unconventional' experiments in biology and medicine with optimized design based on quantum-like correlations. Issue 1 (February 2017) - Beauvais, Francis
Abstract : In previous articles, a description of 'unconventional' experiments (e.g. in vitro or clinical studies based on high dilutions, 'memory of water' or homeopathy) using quantum-like probability was proposed. Because the mathematical formulations of quantum logic are frequently an obstacle for physicians and biologists, a modified modeling that rests on classical probability is described in the present article. This modeling is inspired from a relational interpretation of quantum physics that applies not only to microscopic objects, but also to macroscopic structures, including experimental devices and observers. In this framework, any outcome of an experiment is not an absolute property of the observed system as usually considered but is expressed relatively to an observer. A team of interacting observers is thus described from an external view point based on two principles: the outcomes of experiments are expressed relatively to each observer and the observers agree on outcomes when they interact with each other. If probability fluctuations are also taken into account, correlations between 'expected' and observed outcomes emerge. Moreover, quantum-like correlations are predicted in experiments with local blind design but not with centralized blind design. No assumption on 'memory' or other physical modification of water is necessary in the present description although such hypotheses cannot be formally discarded. In conclusion, a simple modeling of 'unconventional' experiments based on classical probability is now available and its predictions can be tested. The underlying concepts are sufficiently intuitive to be spread into the homeopathy community and beyond. It is hoped that this modeling will encourage new studies with optimized designs for in vitro experiments and clinical trials. Highlights: A modeling of homeopathy clinical trials and in vitro experiments is presented. Interacting observers are described with outcomes expressed relatively to each of them. Quantum-like correlations between 'expected' and observed outcomes emerge. Predictions of this model can be tested.